2016
DOI: 10.1002/jid.3235
|View full text |Cite
|
Sign up to set email alerts
|

In Search of the Pitiful Victim: A Frame Analysis of Dutch, Flemish and British Newspapers and NGO‐Advertisements

Abstract: This article contributes to the ongoing debate on the representation of global poverty in Western media. Both NGOs and journalists are being criticized for their one‐sided emphasis on the misery and dependency of people in developing countries. The objective of this paper is to measure the extent of such problematizing representation in newspaper articles and NGO‐advertisements. A frame analysis was conducted of 876 articles and 284 advertisements from the Netherlands, Flanders and the United Kingdom. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…The specific quotes in Section 4 exemplify these general conditions. However, our findings on the factors influencing the discursive content of face‐to‐face fundraising warrant caution regarding their generalisability beyond the Finnish context because, as Vossen, Van Gorp, and Schulpen () have shown, the discursive tactics of fundraising are country specific.…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…The specific quotes in Section 4 exemplify these general conditions. However, our findings on the factors influencing the discursive content of face‐to‐face fundraising warrant caution regarding their generalisability beyond the Finnish context because, as Vossen, Van Gorp, and Schulpen () have shown, the discursive tactics of fundraising are country specific.…”
Section: Methodsmentioning
confidence: 66%
“…The specific quotes in Section 4 exemplify these general conditions. However, our findings on the factors influencing the discursive content of face-to-face fundraising warrant caution regarding their generalisability beyond the Finnish context because, as Vossen, Van Gorp, and Schulpen (2016) Designing a fundraising campaign begins with selecting the projects and activities that have the highest potential to interest audiences. Our informants revealed that sometimes public opinions about humanitarian action are studied through commissioned research.…”
Section: Methodsmentioning
confidence: 85%
“…The initial inductive frame analysis revealed nine frames, which were labelled "victim", "progress", "social justice", "chain of being", "every man for himself", "blame us", "bad governance", "impending doom" and "global village". Previous investigation into the framing of global poverty in the European media has shown that six frames play a role in the media coverage (Vossen, Van Gorp and Schulpen 2016). The frequency of six frames was measured in a deductive analysis.…”
Section: Frame Analysismentioning
confidence: 99%
“…For example, sociology and political science have looked at a variety of aspects that shape the reporting of news on poverty. This includes examining how issues such as how media campaigns and lobbies from anti‐poverty NGOs and think‐tanks are shaping the news agenda (Bendell, ; Nash, ; Rich & Weaver, ; Seo, Kim, & Yang, ; Vossen, Van Gorp, & Schulpen, ; Waisbord, ; Wright, ) to studying how news on poverty frames the public's perception on health policy (Briggs & Hallin, ; Hinnant, Subramanian, & Jenkins, ; Waisbord, ) and includes areas such as how architecture and urban studies have researched in their own field poverty in the news (Lee et al, ; Petty, ).…”
Section: What We Knowmentioning
confidence: 99%